Perspectives on hospice and palliative care in an academic setting: An exploratory interview study with patients and relatives to inform the development of an academic inpatient hospice - Mareike Löbberding; Heidrun Golla; Anna Wolf; Sukhvir Kaur; Steffen T. Simon; Veronika Dunkl; Julia Strupp; Raymond Voltz; Kerstin Kremeike (PLoS ONE, 2026)
Background Although palliative and hospice care are essential for individuals with life-limiting illnesses, academic inpatient hospices, which combine care with research and education, remain rare. This study explores the experiences, perceptions, and expectations of patients and their relatives regarding palliative and hospice care with the aim of informing the development of an academic inpatient hospice. Methods Semi-structured individual and dyadic interviews were conducted with patients and relatives who had experience with palliative and hospice care services in an academic setting in Germany. The data were analyzed using qualitative content analysis. Results A total of 14 interviews were conducted with 17 participants (10 patients, 7 relatives). Participants reported initial uncertainty and skepticism regarding palliative and hospice care; however, direct experiences led to more positive attitudes. Key aspects valued included psychosocial support, effective symptom management, and a non-clinical atmosphere. The preservation of autonomy and dignity, meaningful personal interactions, and the active involvement of relatives were considered essential. The transition from a hospital-based palliative care unit to an inpatient hospice was often perceived as abrupt and emotionally challenging, creating a risk of losing established familiarity. Participants responded positively to the idea of an academic inpatient hospice. They highlighted the potential benefits of integrating palliative and hospice services within a unified and familiar environment, including smoother transitions and continuity of care. Conclusions An academic inpatient hospice offers opportunities to address end-of-life care needs by strengthening existing structures and ensuring continuity and comprehensiveness of care. It can support patient-centered care, provide a platform for education and research, and promote greater public awareness and understanding of palliative and hospice care.